Nilai-nilai Pendidikan Akhlaq dalam Kitab Idhotun Nasyi’in Karya Syekh Musthofa Al-Ghalayain - Qulniyah Qulniyah; Robingun Suyud El Syam; Nur Farida (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Morals are a condition that is inherent in the human soul, which gives birth to actions. If this situation gives rise to good and commendable actions according to reason and Islamic law, it is called good morals. If the actions that arise are not good, they are called bad morals. The research carried out is included in the category of library research, library research is a type of research using literature (libraries) in the form of books, notes, or reports of relevant previous research results, to obtain answers and theoretical basis regarding the problem to be researched. The library method is a type of qualitative research method. Library study research is carried out by researchers to solve a problem that relies on an in-depth review of relevant library materials. The data sources used are primary data sources and secondary data sources. Data collection techniques used include documentaries and online data documentation. Data analysis techniques, content analysis and discourse analysis. From the research results it can be concluded that 1) To find out the values of moral education in the book Idhotun Nasyi’ in the work of Syekh Musthofa Al-Ghalayain. 2) to find out the relevance of moral education from the perspective of Sheikh Musthofa Al-ghalayain today.